An Assessment of Itsekiri Middlemen, the Rise of Sapele and Its Negative Effects on the Benin Trade with the Europeans, 1593-1897 - Ediagbonya Michael (Britain International for Academic Research (BIAR) Publisher, 2023)
The paper examines Itsekiri Middlemen, the rise of Sapele and its negative effects on the Benin trade with the Europeans. It discusses the shifting of trade from Ughoton to the factories or warehouses nearer the sea by the Dutch. It assessed the factors behind Dutch’s action. It demonstrated the role played by Itsekiri in the British invasion of Benin in 1897. The data was obtained from primary and secondary sources. Oral interview constitutes the primary sources. Books, newspapers, articles, theses, dissertation etc were used as secondary sources. The study found that the shifting of trade from Ughoton to the factories nearer the sea affected Benin-European trade negatively. It was also found that the purpose of the Dutch shifting the trade to factories along the main Benin River was to reduce the control of Oba of Benin over the trade. It was demonstrated that the Itsekiri now possessed more power and they contributed to the British invasion of Benin in 1897. It concludes that the sudden rise of Sapele was due to the establishment of the vice-consulate of the Benin River in the town.